Influence of nanogold additives on phase formation, microstructure and dielectric properties of perovskite BaTiO3 ceramics - Nonkumwong,J. (Springer Heidelberg, 2015)
© 2015 Springer-Verlag Berlin Heidelberg The formation of perovskite phase, microstructure and dielectric properties of nanogold-modified barium titanate (BaTiO3) ceramics was examined as a function of gold nanoparticle contents by employing a combination of X-ray diffraction, scanning electron microscopy, energy-dispersive X-ray, Archimedes principle and dielectric measurement techniques. These ceramics were fabricated from a simple mixed-oxide method. The amount of gold nanoparticles was found to be one of the key factors controlling densification, grain growth and dielectric response in BaTiO3 ceramics. It was found that under suitable amount of nanogold addition (4 mol%), highly dense perovskite BaTiO3 ceramics with homogeneous microstructures of refined grains (~0.5–3.1 μm) and excellence dielectric properties can be produced.